PENEGAKAN HUKUM TERHADAP KEJAHATAN TERORISME SEBAGAI ‘EXTRAORDINARY CRIME’ DALAM PERSPEKTIF HUKUM INTERNASIONAL DAN NASIONAL - Aulia Rosa Nasution (deliberatif, 2017)
This paper aims to review the acts of terrorism as an ‘extraordinary crime’ in the perspective of the international and national law. The approach methodology of this research usesthe juridical normative methodology which is conducted by analyzing and reviewing the international conventions on terrorismand theanti terrorism law in Indonesia specially the Act No. 15/2003 on Combating Terrorism Acts. Terrorism has become one of the national threat for Indonesia and for the world globally because it destroyed civilians people physically and mentally. Terrorism often occurred in the international and national scope, which has negative impacts for the stability and the security in Indonesia. In an effort to counter the acts of terrorism, Indonesian government has ratified several anti terrorism conventions. Indonesian government also has declared its commitment to combat all forms of terrorism acts which has been set in the Act No. 15/2003 on Combating Terrorism Acts. One of the considerations in the creation of the anti terrorism law in Indonesia is because the acts of terrorism has its own characteristic which isvery different from other ordinary crimes and causes it to be categorized as an ‘Extraordinary crime’.